Writing About Writing: Reading Academia Anew - Trevor Norris (Brock University, 2024)
Since the inauguration of the first European universities in the medieval era, at Bologna in 1088 and Oxford in 1096, and before that, al-Qarawiyyin in 859 in Fez, Morocco, Nalanda University in 5th century India, and Taixue University in China in 156, universities have been places of publishing, writing, and disseminating scholarly ideas. Socrates, who himself wrote nothing, worried in 400 B.C.E. that writing would weaken the mind, promote forgetfulness (Ong, 2002), and allow for the pretention of knowledge rather than the real thing, "the appearance of wisdom, not true wisdom" (Plato, 370 B.C.E./1901,Phaedrus, section 275a).